Infecção de células fagocíticas não-profissionais epiteliais pelo Trypanosoma cruzi mediada através da ativação de NF-kB induzida pelo fator de necrose tumoral (TNF) - Andrea Moraes Torres Pinto (2011)
At the site of infection, pro-inflammatory cytokines locally produced by macrophages infected with Trypanosoma cruzi can activate surrounding nonprofessional phagocytes such as fibroblasts, epithelial and endothelial cells, which can be further invaded by the parasite. The effect of secreted soluble factors on the invasion of these cells remains, however, to be established. We show here that two epithelial cell lines become significantly susceptible to the infection by the Y strain of T. cruzi after tumor necrosis factor (TNF) treatment. The increase in the invasion was correlated with the increasing concentration of recombinant TNF added to cultures of HEK293T or LLC-MK2 cells. Supernatants taken from PMAdifferentiated human monocytes infected with T. cruzi also increased the permissiveness of epithelial cells to subsequent infection with the parasite, which was inhibited by a TNF monoclonal antibody. Furthermore, the permissiveness induced by TNF was inhibited by TPCK, and led to significant decrease in the number of intracellular parasites, providing evidence that activation of NF-κB induced by TNF favors the invasion of the epithelial cell lines by T. cruzi through yet an unidentified mechanism. Our data indicate that soluble factors released from macrophages early in the infection favors T. cruzi invasion of non-professional phagocytic cells.